Therapeutic efficacy and mechanisms of Xuebijing in Acinetobacter baumannii infection based on meta-analysis and integrated pharmacology approaches - Li, Jiaqi; Sun, Yihan; Wen, Hao; Xiao, Boying; Wang, Jianming; Li, Ziqi; Wang, Lei; Yu, Meiyu (Frontiers in Pharmacology, 2025)
BackgroundXuebijing (XBJ) is a traditional Chinese medicine widely used in China for managing sepsis, systemic inflammatory response syndrome, and multiple organ dysfunction secondary to severe infections. This study aimed to assess the therapeutic efficacy and safety of XBJ as an adjuvant treatment for Acinetobacter baumannii (A. baumannii) infections through meta-analysis, and to explore its potential mechanisms via integrated pharmacological approaches.Materials and methodsA systematic search was conducted across multiple databases for randomized controlled trials (RCTs) evaluating XBJ in A. baumannii infections up to 9 February 2025. Meta-analyses were conducted to synthesize clinical outcomes, and evidence certainty was assessed using the GRADE framework. Network pharmacology, molecular docking, and molecular dynamics simulations were used to evaluate the interactions between active ingredients of XBJ and protein targets in A. baumannii infections.ResultsA total of 11 RCTs involving 1,035 patients met the inclusion criteria. Meta-analysis demonstrated that XBJ significantly improved clinical outcomes, with a higher overall effective rate (RR = 1.20, 95% CI: 1.13–1.27, P < 0.01) and enhanced bacterial clearance (RR = 1.44, 95% CI: 1.23–1.68, P < 0.01) compared to conventional treatment alone. Additionally, XBJ treatment was associated with marked reductions in inflammatory markers, including C-reactive protein (CRP) (SMD = −2.12), procalcitonin (PCT) (SMD = −2.28), and white blood cell (WBC) count (SMD = −1.00) (all P < 0.01). Notably, no serious adverse drug events were reported. Mechanistic investigations identified three active ingredients of XBJ including scutellarin, salvianolic acid C, and isosalvianolic acid C, as potential modulators of MMP9 and TLR4, suggesting the role of XBJ in attenuating inflammatory responses and improving infection outcomes.ConclusionXBJ appears effective and safe as an adjuvant therapy for A. baumannii infections, but further high-quality RCTs are warranted to validate these findings.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023486389.